2023
DOI: 10.1097/phm.0000000000002240
|View full text |Cite
|
Sign up to set email alerts
|

Handrim Wheelchair Propulsion Technique in Individuals With Spinal Cord Injury With and Without Shoulder Pain

Abstract: Objective The aim of this study was to compare handrim wheelchair propulsion technique between individuals with spinal cord injury with and without shoulder pain. Design A cross-sectional study including 38 experienced handrim wheelchair users with spinal cord injury was conducted. Participants were divided into the “shoulder pain” (n = 15) and “no-shoulder pain” (n = 23) groups using the Local Musculoskeletal Discomfort scale. Kinetic and spatiotempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therapies with an increased musculoskeletal load have proven effective; however, this approach is limited in patients who are wheelchair-bound after SCI. Stand-up wheelchairs, standing frames, and suspended treadmills can provide useful alternatives [ 11 , 111 , 112 ]. Physical activity, which inherently stimulates the axial loading of the tibia, femur, and axial skeleton, may also promote bone density after SCI by improving bone vascularization and osteoblast activity [ 4 , 112 ].…”
Section: Therapeutic Strategies For Neurogenic Bone Loss After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Therapies with an increased musculoskeletal load have proven effective; however, this approach is limited in patients who are wheelchair-bound after SCI. Stand-up wheelchairs, standing frames, and suspended treadmills can provide useful alternatives [ 11 , 111 , 112 ]. Physical activity, which inherently stimulates the axial loading of the tibia, femur, and axial skeleton, may also promote bone density after SCI by improving bone vascularization and osteoblast activity [ 4 , 112 ].…”
Section: Therapeutic Strategies For Neurogenic Bone Loss After Scimentioning
confidence: 99%
“…Stand-up wheelchairs, standing frames, and suspended treadmills can provide useful alternatives [ 11 , 111 , 112 ]. Physical activity, which inherently stimulates the axial loading of the tibia, femur, and axial skeleton, may also promote bone density after SCI by improving bone vascularization and osteoblast activity [ 4 , 112 ].…”
Section: Therapeutic Strategies For Neurogenic Bone Loss After Scimentioning
confidence: 99%
“…Because of the strenuous nature of wheelchair sports with respect to the shoulder, shoulder pain is common among wheelchair athletes. Braaksma et al performed a cross-sectional study analyzing different wheelchair propulsion techniques among those with and without shoulder pain 35 . They found that individuals with a spinal cord injury who experience shoulder pain propel their wheelchairs kinematically differently from those who do not experience pain; the pain group had a shorter cycle time, shorter recovery time, smaller contact angle, and lower variability in work performed per push compared with the group that did not experience pain.…”
Section: Parasportsmentioning
confidence: 99%